PENGARUH KREASI NILAI TERHADAP KINERJA BPR DI JAWA BARAT - A.V Rahajeng Widyarsih; Yohanes Ferry Cahaya; Annathasia Puji Erasashanti (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
BPR has a big role to drive the regional economy. The financial performance of rural banks in West Java generally tends to improve, but is not in line with the growth in the number of rural banks, which shows a declining trend from year to year. In addition, the growth of third-party funds (DPK) gradually slowed down from 25.70% in 2009 to 8.10% in 2015 and 0.69% in August 2016. The condition is thought to be related to problems in developing value creation. So, this study aims to examine the effect of value creation on BPR performance in West Java. This research uses a quantitative research approach. Observations were made in the time section which is cross section / one shot, that is in 2019. The analysis unit is BPR in West Java, with the observation unit that is the management of the BPR in the West Java Province. Data taken from a sample of 100 respondents and analyzed using PLS. The results showed that value creation had a significant influence on the performance of BPR in West Java. This finding is expected to be an alternative model for BPR management in West Java that improving BPR performance relies on developing value creations especially in the business partner aspect, supported by business domain development and customer benefits.